The influence of the dynamics features of the trapped particles on a spectrum of their oscillations - Buts, V.A.; Vavriv, D.M.; Tarasov, D.V. (Вопросы атомной науки и техники, 2013)
Some features of dynamics of ensembles of coupled linear and nonlinear oscillators are investigated. It is shown that spectral characteristics of this dynamics essentially depend not only on quantity of the oscillators making the ensemble, but also on features of motion of each oscillator. In particular, at chaotic motion – on the moments of their chaotic dynamics. Special attention is turned on appearance of LF dynamics of ensemble. In this case there is a possibility of an effective exchange of energy between HF and LF oscillations. Досліджені особливості динаміки ансамблів зв'язаних лінійних і нелінійних осциляторів. Показано, що спектральні характеристики цієї динаміки суттєво залежать не тільки від кількості осциляторів, складових ансамблю, але й від особливостей руху кожного осцилятора. Зокрема, при хаотичному русі – від моментів їх хаотичної динаміки. Особливе значення звернено на виникнення НЧ-динаміки ансамблю. У цьому випадку з'являється можливість ефективного обміну енергією між ВЧ- і НЧ-коливаннями. Исследованы особенности динамики ансамблей связанных линейных и нелинейных осцилляторов. Показано, что спектральные характеристики этой динамики существенно зависят не только от количества осцилляторов, составляющих ансамбль, но и от особенностей движения каждого осциллятора. В частности, при хаотическом движении – от моментов их хаотической динамики. Особое значение обращено на возникновение НЧ-динамики ансамбля. В этом случае появляется возможность эффективного обмена энергией между ВЧ- и НЧ-колебаниями.